2017
DOI: 10.1590/1518-8345.1950.2954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ineffective breathing pattern and impaired spontaneous ventilation of adults with oxygen therapy

Abstract: Objective:to analyze the manifestation of the defining characteristics of the nursing diagnoses of ineffective breathing pattern and impaired spontaneous ventilation, of the NANDA International and the defining characteristics identified in the literature for the concept of “ventilation” in adult patients hospitalized in an intensive care unit with use of oxygen therapy. Method:clinical diagnostic validation study, conducted with 626 patients in intensive care using oxygen therapy, in three different modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 13 publications
0
17
0
5
Order By: Relevance
“…A recent study, also performed in an ICU in the city of Ribeirão Preto, SP, Brazil, with 626 adult patients, showed that the RF fatigue presented greater sensitivity for the IBP diagnosis 23 . The authors emphasize that IBP patients present DC related to ventilatory dysfunction and, if not treated adequately, this diagnosis may evolve to the diagnosis of impaired spontaneous ventilation (ISV), characterizing a worse prognosis of the patient 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study, also performed in an ICU in the city of Ribeirão Preto, SP, Brazil, with 626 adult patients, showed that the RF fatigue presented greater sensitivity for the IBP diagnosis 23 . The authors emphasize that IBP patients present DC related to ventilatory dysfunction and, if not treated adequately, this diagnosis may evolve to the diagnosis of impaired spontaneous ventilation (ISV), characterizing a worse prognosis of the patient 23 .…”
Section: Discussionmentioning
confidence: 97%
“…The DC decreased inspiratory pressure evaluated by the manovacuometer was chosen to confirm the presence of IBP because a study conducted in 2015 and 2016 with 626 adult ICU patients showed that this DC and the RF fatigue were the ones that had the greatest sensitivity for the IBP diagnosis in these patients 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Clusters of DC are also recommended by NANDA‐I taxonomy II, suggesting that to achieve accuracy in certain diagnoses it is necessary to analyze a group of signs and symptoms (Herdman & Kamitsuru, ). Furthermore, grouping of DC for respiratory ND has been recently proposed in a study that aimed to analyze through a latent class model DC for ISV and IBP (Seganfredo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the identification of respiratory deterioration is a priority in nurses' assessment (Borgert et al, 2015;Mc-Coll & Pesata, 2016), assessment of these needs is not always reflected in accurate ND because there are factors that make this process difficult, such as the similarity among the respiratory diagnoses. Accuracy studies examining the association between DC and the respective respiratory ND have been performed with diverse patient populations, such as adult postoperative period of cardiac surgery patients (Sousa et al, 2015(Sousa et al, , 2016, intensive care unit (ICU) patients (Seganfredo et al, 2017), and in newborns (Avena, Pedreira, Alves, Herdman, & Gutierrez, 2019). Overall, previous studies have explored which DC better predicts the presence/absence of their respective ND.…”
Section: Background and Purposementioning
confidence: 99%
“…A CD pressão inspiratória diminuída avaliada pelo manovacuômetro foi escolhida para confirmar a presença de PRI, pois um estudo realizado em 2015 e 2016, com 626 pacientes adultos em UTI mostrou que essa CD e o FR fadiga foram os fatores que apresentaram maior sensibilidade para o diagnóstico PRI nesses pacientes (23) . A enfermeira responsável por esta pesquisa coletou os dados com a ajuda de um instrumento padronizado elaborado para esse fim.…”
Section: Métodounclassified